2007
DOI: 10.1556/abiol.58.2007.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Acetylsalicylic acid decreases the labeling of blood constituents with technetium-99m

Abstract: Acetylsalicylic acid is the most widely used drug as antipyretic, analgesic, anti-inflammatory agent and for secondary prevention of thrombotic phenomena in the heart, brain and peripheral circulation. Drugs can modify the labeling of blood constituents with technetium-99m (99mTc). This work has evaluated the effect of in vivo treatment with acetylsalicylic acid on the in vitro labeling of the blood constituents with 99mTc. Wistar rats were treated with different doses (1.5, 3.0 and 6.0 mg/kg) of acetylsalicyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…Blood constituents labeled with 99mTc have been used in several clinical examinations (Saha, 2004) and also as an experimental assay on an attempt to verify the effect of drugs ). This experimental model has permitted to obtain relevant information about properties of various chemical compounds (synthetic and natural) (Abreu et al, 2006;Fonseca et al, 2007). The analysis of the results shown in tables 1, 2 and 3 indicates that there was an important alteration on the labeling of the blood constituents with 99m…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood constituents labeled with 99mTc have been used in several clinical examinations (Saha, 2004) and also as an experimental assay on an attempt to verify the effect of drugs ). This experimental model has permitted to obtain relevant information about properties of various chemical compounds (synthetic and natural) (Abreu et al, 2006;Fonseca et al, 2007). The analysis of the results shown in tables 1, 2 and 3 indicates that there was an important alteration on the labeling of the blood constituents with 99m…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells labeled with technetium-99m (99mTc-RBC) are widely used in clinical nuclear medicine for several important applications (Wong et al, 2004;Jin et al, 2004;Zaman et al, 2004;Artiko et al, 2004;Harel et al, 2005;Verdu et al, 2005;Olds et al, 2005). The labeling of RBC with 99mTc has been used as assay to evaluate the properties of different chemical agents (Abreu et al, 2006;Fonseca et al, 2007). The radiolabeling depends on the presence of a reducing agent and stannous chloride is widely utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have been reported that natural and synthetic drugs could alter the labeling of blood constituents with 99mTc (Frydman et al, 2004;Abreu et al, 2006;Fonseca et al, 2007). The labeling of blood constituents would decrease due to the action of drugs that could (1) bind at the same sites of 99mTc on the blood constituents, (2) directly inhibit (chelating action) of the stannous and pertechnetate ions, (3) oxidize or generate free radicals that could oxidize the stannous ion, and (4) alter the plasma membrane structure or modify the transport systems of stannous and pertechnetate ions into cells.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cells labeled with technetium-99m ( 99m Tc) are also employed in diagnostic procedures (Saha, 2004). Drugs (natural and synthetic) could alter the biodistribution of radiopharmaceuticals and the labeling of blood constituents with 99m Tc (Bernardo-Filho et al, 2005;Fonseca et al, 2007. This study evaluates biological effects of a CA extract on the biodistribution of the radiopharmaceutical Na 99m TcO 4 and on the fixation of the radioactivity on blood constituents.…”
Section: Introductionmentioning
confidence: 99%